Pengaruh Jumlah Penduduk dan Pengangguran Terhadap Tingkat Kemiskinan di Kabupaten Muara Bungo - Alian (PENG: Jurnal Ekonomi dan Manajemen, 2024)
This research is to determine the effect of population and poverty on the poverty level in Muara Bango Regency. This research is included in associative research with the data sources used, namely primary data and secondary data. Data analysis uses quantitative data analysis methods with multiple linear regression analysis tools. The research results showed that population had a positive but not significant effect on the poverty level in Muara Bungo Regency, while unemployment also had a positive but not significant effect on the poverty level in Muara Bungo Regency. Taken together, population and poverty do not have a significant influence on poverty in Muara Bungo Regency.